Dietary intakes and dietary patterns among pregnant women in Northwest China. Issue 2 (30th August 2016) - Yang, Jiaomei; Dang, Shaonong; Cheng, Yue; Qiu, Huizhen; Mi, Baibing; Jiang, Yufen; Qu, Pengfei; Zeng, Lingxia; Wang, Quanli; Li, Qiang; Kang, Yijun; Shen, Yuan; et al.
Abstract: Objective: To describe nutrient intakes, characterize dietary patterns and analyse their associations with sociodemographic characteristics among pregnant women in Shaanxi, China. Design: Population-based cross-sectional survey. Setting: Twenty counties and ten districts in Shaanxi Province of Northwest China, 2013. Subjects: Women ( n 7462) were recruited using a stratified multistage random sampling method to report diets during pregnancy, at 0–12 months (median 3 months; 10th–90th percentile, 0–7 months) after delivery. Results: Pregnant women had higher intakes of fat, niacin and vitamin E than the nutrient reference values, while most micronutrients such as vitamin A, folate, Ca and Zn were reportedly low. Women in the highest education, occupation and household income groups had higher nutrient intakes than those in the lowest groups. Nutrient intake differences also existed by geographic area, residence and maternal age at delivery. Three dietary patterns were identified: balanced pattern, vegetarian pattern and snacks pattern. Participants with high balanced pattern scores tended to be better educated, wealthier, 25–29 years old at delivery, working outside and living in urban areas and central Shaanxi. Women with high scores on the vegetarian pattern and snacks pattern tended to be in low balanced pattern score groups, and had lower nutrient intakes than those in the high balanced pattern score groups. Conclusions: The study suggested that pregnant women in Shaanxi, China had low intakes of most nutrients such as vitamin A, folate and Ca. Dietary patterns and most nutrient intakes varied by sociodemographic characteristics. Targeted programmes are needed to improve dietary intakes and dietary patterns among sociodemographically disadvantaged groups.